Optimalisasi Pembelajaran Tahfidz al-Qur'an dengan Metode Taḥfīẓ Sabaq, Sabqi, Manzil di Madrasah Ibtidaiyah Lit Taḥfīẓil Qur’ān Jamilurrohman - Eko Ngabdul Shodikin; Muh. Wasith Achadi (ISLAMIKA, 2023)
One common difficulty those who memorize the Qur'an faces is the challenge of retaining what they have memorized. To address these challenges, various Taḥfīẓ methods have emerged to facilitate the process of memorization. One of the methods that has been implemented in several Islamic boarding schools is the Sabaq, Sabqi, and Manzil (SSM) method. One primary school that applies this method is the Madrasah Ibtidaiyah Lit Taḥfīẓil Qur’ān Jamilurrohman (MITQ) Jamilurrohman. This research aims to investigate how the implementation of the SSM Taḥfīẓ method can help students overcome difficulties in improving their Qur'anic memorization and assist teachers in teaching Taḥfīẓ Al-Qur’ān. This research employs a descriptive qualitative approach using observation, interviews, and documentation to collect data. The data analysis process follows the steps developed by Miles and Huberman, including data reduction, data presentation, and conclusion drawing. Triangulation techniques, such as source and data triangulation, are used to validate the findings. The results indicate that the implementation of the SSM method in Taḥfīẓ learning at MITQ involves three stages: planning, implementation, and evaluation. The findings show that the SSM method improves students' memorization and comprehension of the Qur'an, as well as an overall enhancement in the quality of Taḥfīẓ learning.